Academic Spin Doctoring: The Incommensurability Debate as a Scholarly War Fantasy. Issue 4 (November 2018) - Lowe, Sid; Rod, Michel
This commentary to Shaw and Nowicki (2018) proposes that academic paradigms are 'dialogical' discourses that both compete and collaborate in order to sustain their identities. They are all based on different underlying assumptions and are carried by different symbols, tropes and narratives. Each version of the truth cultivates an identity that principally depends upon it not being its alternative. As a result, each paradigm depends upon the continued existence of its opposite. In this sense, therefore, the paradigm wars were a concocted dispute over invented territories and contrived opponents. The contribution of the paper for those seeking paradigmatic peace is to emphasise that just as the war was a concocted 'simulacrum', any peace must also be designed as fantasies accomplished through language games.